DECISION MAKING TO DETERMINE BEST ALTERNATIVE TO PREVENT PRODUCTION LOSS RELATED TO VAPOR RECOVERY UNIT (VRU) DOWNTIME AT PT XYZ INDONESIA - Kurniaputera Artanto, Alif
Currently, PTN Gas Plant processes associated gas from the gas boot of PTN Gathering Station. The associated gas is processed through the Vapor Recovery Unit (VRU) gas compressor before further handled by the larger AWE gas compressor. After the gas is compressed, cooled and separated it is then delivered through the outgoing pipeline and towards the gas turbines where it will be utilized as fuel to produce electricity for the operation.